Novel Bacterial Diversity and Fragmented eDNA Identified in Hyperbiofilm-Forming Pseudomonas aeruginosa Rugose Small Colony Variant - Binbin Deng; Subhadip Ghatak; Subendu Sarkar; Kanhaiya Singh; Piya Das Ghatak; Shomita S. Mathew-Steiner; Sashwati Roy; Savita Khanna; Daniel J. Wozniak; David W. McComb; Chandan K. Sen (iScience, 2020)
Summary: Pseudomonas aeruginosa biofilms represent a major threat to health care. Rugose small colony variants (RSCV) of P. aeruginosa, isolated from chronic infections, display hyperbiofilm phenotype. RSCV biofilms are highly resistant to antibiotics and host defenses. This work shows that RSCV biofilm aggregates consist of two distinct bacterial subpopulations that are uniquely organized displaying contrasting physiological characteristics. Compared with that of PAO1, the extracellular polymeric substance of RSCV PAO1ΔwspF biofilms presented unique ultrastructural characteristics. Unlike PAO1, PAO1ΔwspF released fragmented extracellular DNA (eDNA) from live cells. Fragmented eDNA, thus released, was responsible for resistance of PAO1ΔwspF biofilm to disruption by DNaseI. When added to PAO1, such fragmented eDNA enhanced biofilm formation. Disruption of PAO1ΔwspF biofilm was achieved by aurine tricarboxylic acid, an inhibitor of DNA-protein interaction. This work provides critical novel insights into the contrasting structural and functional characteristics of a hyperbiofilm-forming clinical bacterial variant relative to its own wild-type strain. : Microbiology; Microbiofilms Subject Areas: Microbiology, Microbiofilms